2012
DOI: 10.1111/j.1365-2621.2012.03192.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth promotion of Bifidobacterium and Lactobacillus species by proteinaceous hydrolysates derived from poultry processing leftovers

Abstract: Summary Bacterial growth media represent a high cost in industrial applications, and for this reason, it is economically important to find less expensive supplements to replace the traditional ones. In the present work, peptide hydrolysates obtained from poultry meat and bone residues (functional animal protein [FAP]) and from feathers (functional feather protein [FFP]) were studied to determine their ability for the production of microbial biomass with improved viability. The results obtained were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Furthermore, the mortadella-type sausages containing MDCM protein hydrolysates also had higher (P < 0.05) LAB counts on days 15 and 45 of storage when compared to those of the CT. Lazzi et al (2011) showed that the addition of protein hydrolysate obtained from the poultry industry promoted the growth of a wide range of Bifidobacterium species of human origin. Recently, Lazzi et al (2013) also reported that the growth of Lactobacillus species could also be improved by the supplementation with proteinaceous hydrolysates derived from poultry processing leftovers. These studies showed that protein hydrolysates from poultry meat are a promising functional food, and this is probably one of the reasons why the treatments with MDCM protein hydrolysate addition showed higher LAB counts when compared to those of the control treatment.…”
mentioning
confidence: 99%
“…Furthermore, the mortadella-type sausages containing MDCM protein hydrolysates also had higher (P < 0.05) LAB counts on days 15 and 45 of storage when compared to those of the CT. Lazzi et al (2011) showed that the addition of protein hydrolysate obtained from the poultry industry promoted the growth of a wide range of Bifidobacterium species of human origin. Recently, Lazzi et al (2013) also reported that the growth of Lactobacillus species could also be improved by the supplementation with proteinaceous hydrolysates derived from poultry processing leftovers. These studies showed that protein hydrolysates from poultry meat are a promising functional food, and this is probably one of the reasons why the treatments with MDCM protein hydrolysate addition showed higher LAB counts when compared to those of the control treatment.…”
mentioning
confidence: 99%
“…Soluble protein fractions in Carapax Trionycis could also contribute to its prebiotic potential. Some studies have reported that lactobacillus and bifidobacteria growth was stimulated by bone and meat residues due to their high peptides and free amino acids . In fact, lactobacilli is typical multiple amino acids auxotrophs bacterium, and its growth is closely related to the amount and quality of amino acids in the culture medium .…”
Section: Discussionmentioning
confidence: 99%
“…Calcium in animal bones mainly exists in the forms of hydroxyapatite crystals and amorphous calcium hydrogen phosphate wrapped by collagen fibers, but dense tissues cannot be absorbed easily by the body . Much effort has been made to modify bone, including high pressure, enzymolysis, and acid hydrolysis methods . However, high‐pressure cooking in the presence of water can lead to the loss of a large amount of nutrients .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations